Claiming Her Dignity : Female Resistance in the Old Testament - Claassens, L. Juliana M., 1972- (Book collections on Project MUSE., 2016)
To be human means to resist dehumanization. In the darkest periods of human history, men and women have risen up and in many different voices said this one thing: "Do not treat me like this. Treat me like the human being that I am." Claiming Her Dignity explores a number of stories from the Old Testament in which women in a variety of creative ways resist the violence of war, rape, heterarchy, and poverty. Amid the life-denying circumstances that seek to attack, violate, and destroy the bodies and psyches of women, men, and children, the women featured in this book absolutely refuse to succumb to the explicit, and at times subtle but no less harmful, manifestations of violence that they face. (Publisher).